Act and Being - Bonhoeffer, Dietrich, 1906-1945 (Book collections on Project MUSE., 1996)
Dietrich Bonhoeffer Works series is the definitive English translation of the German editions of Dietrich Bonhoeffer Werke--a comprehensive and thoroughly annotated sixteen-volume resource for the study of Bonhoeffer in the wider frame of twentieth-century thought and history. --